Design, synthesis and DNA/RNA binding studies of nucleic acids comprising stereoregular and acyclic polycarbamate backbone: polycarbamate nucleic acids (PCNA) - Madhuri, Vangala; Kumar, Vaijayanti A. (Organic & Biomolecular Chemistry, 2010)
The designed, chiral, acyclic polycarbamate nucleic acids (PCNA) exhibited sequence and orientation specific binding to nucleic acids. Complexes of PCNA with DNA were as stable as PNA:DNA complexes and those with RNA were as stable as natural DNA:RNA complexes.

Design and synthesis of dephosphono dna analogues containing 1,2,3-triazole linker and their UV-melting studies with DNA/RNA - Madhuri, Vangala; Kumar, Vaijayanti A. (Nucleosides Nucleotides & Nucleic Acids, 2012)
This article describes the synthesis of 3'/5' linked 1,2,3-triazolyl dithymidine derivatives, their incorporation into oligonucleotides, and evaluation of their thermal stabilities toward complementary DNA/RNA.
Keywords: isostere; Oligonucleotide analogues; Triazole; UV melting